Making Finance Work for Nigeria - World Bank (Washington, DC, 2017)
This study begins by considering the banking sector and then moves on to issues relating to improving access to finance to support Nigeria's economic growth vision. The second part of the study refers to issues relating to longer-term finance: both the sources of financing, such as pensions and insurance, and their uses in providing financing for resolving Nigeria's crucial infrastructure shortfalls in infrastructure and housing. The final part of the study returns to the fundamental 'plumbing' of the financial system focusing on the legal and regulatory foundation for creditor rights and corporate insolvency, instituting sound corporate governance standards for corporations and banks, and providing secure and low cost transmittal of payments and remittances. While it is difficult to identify a common theme running through this volume without compromising the diversity and nuance of the recommendations, the overarching theme supported by this volume is the importance of exchange of reliable information as the basis for financial transactions between unconnected third parties. Implementation of systems designed to strengthen accounting and reporting standards for banks and corporations, the registration of movable and immovable property, property liens and credit histories as well as exchange of information about prices, interest rates, fees and charges for financials services will considerably enhance the functionality of financial systems and prove crucial in establishing a trusted and robust market-based financial system in support of stable economic growth and development in Nigeria.